What the luck? : the surprising role of chance in our everyday lives - Smith, Gary, 1945- (Overlook Press, 2016)
Explores the role of luck, specifically the concept of "regression to the mean," in everyday life, exploring how failures to understand chance and random variations influence choices and perceptions of truth.